DETERMINATION OF DOXORUBICIN HYDROCHLORIDE IN PHARMACEUTICA DOSAGE FORMS BY A SIMPLE STABILITY-INDICATING MICELLAR ELECTROKINETIC CAPILLARY CHROMATOGRAPHY METHOD - Daniele Rubert Nogueira-Librelotto; Laís Engroff Scheeren; Clarice Madalena Bueno Rolim; Letícia Bueno Macedo; Joana Rodrigues Fernandes (Drug Analytical Research, 2019)
A stability-indicating micellar electrokinetic capillary chromatography (MEKC) method was developed and validated for the analysis of doxorubicin hydrochloride in injectable pharmaceutical dosage forms, using methotrexate as internal standard. A fused-silica capillary (50 µm i.d.; effective length, 40 cm) and a running electrolyte solution consisting of 10 mM borate buffer and 20 mM anionic surfactant SDS, at pH 9.3, were set as the best experimental conditions. Moreover, the capillary temperature was maintained at 26 ºC, while the applied voltage was +26 kV. Hydrodynamic sample injection (6 s at 50 mbar) was used, and the detection was set at 260 nm using a photodiode array detector. The method was validated for the requirements specificity, linearity, precision, accuracy, and robustness, following the International Conference on Harmonisation (ICH) guidelines. The method linearity was proven in the range of 25-125 µg/mL (r = 0.9995). Forced degradation studies were successfully conducted, evidencing the specificity and stability-indicating capability of the method. In addition, no interference of the excipients from the formulation was detected. The values of accuracy and precision were within the acceptable limits, and robustness studies were performed by a two-level full factorial design. The proposed method fulfilled all validation parameters and was shown to be suitable for quantitative analyses of doxorubicin, contributing, thus, to the establishment of new alternatives with advantages for the quality control of pharmaceutical formulations.